Metal-free C–H alkylation of heteroarenes with alkyltrifluoroborates: a general protocol for 1°, 2° and 3° alkylation. Issue 5 (6th March 2017) - Matsui, Jennifer K.; Primer, David N.; Molander, Gary A.
Abstract : A photoredox-catalyzed C–H functionalization of heteroarenes using a variety of primary, secondary, and tertiary alkyltrifluoroborates is reported. Abstract : A photoredox-catalyzed C–H functionalization of heteroarenes using a variety of primary, secondary, and tertiary alkyltrifluoroborates is reported. Using Fukuzumi's organophotocatalyst and a mild oxidant, conditions amenable for functionalizing complex heteroaromatics are described, providing a valuable tool for late-stage derivatization. The reported method addresses the three major limitations of previously reported photoredox-mediated Minisci reactions: (1) use of superstoichiometric amounts of a radical precursor, (2) capricious regioselectivity, and (3) incorporation of expensive photocatalysts. Additionally, a number of unprecedented, complex alkyl radicals are used, thereby increasing the chemical space accessible to Minisci chemistry. To showcase the application in late-stage functionalization, quinine and camptothecin analogues were synthesized. Finally, NMR studies were conducted to provide a rationalization for the heteroaryl activation that permits the use of a single equivalent of radical precursor and also leads to enhanced regioselectivity. Thus, by 1 H and 13 C NMR a distinct heteroaryl species was observed in the presence of acid catalyst and BF3 .